Confirmatory Factor Analysis of the Hip Disability and Osteoarthritis Outcome Score (HOOS) and Associated Sub-scales - Emilie N. Miley; Madeline P. Casanova; Scott W. Cheatham; Lindsay Larkins; Michael A. Pickering; Russell T. Baker (International Journal of Sports Physical Therapy)
# Background